LUMBAR STENOSIS IN SYMPTOMATIC BACKACHE PATIENTS OF MORE THAN 50 YEARS AGE - Panezai, Abdul Samad; Kalhoro, Aurangzeb; Khan, Sher Hassan; Javed, Farrukh; Rehman, Lal (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the frequency of Lumbar Stenosis in symptomatic backache patients of more than 50 years age. Methodology: This descriptive cross sectional study was conducted in Department of Neurosurgery, Jinnah Postgraduate Medical Centre, Karachi, on 169 patients having symptoms from Feb 2017 to January 2019. Non-probability consecutive sampling was used to enroll the sample. After following the ethical practices, taking informed written consent, the pre-designed performa was filled along with the complete history and the examination. Magnetic Resonance Imaging (MRI) lumbosacral spine was advised and patients with lumbar spinal stenosis based on their history, MRI and examination were reported by the consultant radiologist. Results: In total of 169 participants, the mean age was recorded to be 63±8.40 years, wherein 67 (39.6%) females and 102 (60.3%) were males. The frequency of spinal stenosis diagnosed on imaging in symptomatic patients was recorded to be as 37.3% (n=63). A significant relationship was recorded between gender and professions with LSS (p-value = <0.05), whereas age group and BMI had an insignificant relationship (p-value = >0.05). Conclusion: The study concluded that 37% of the participants with any symptoms were diagnosed as LSS. Furthermore, a positive relationship was determined between gender and profession with LSS.